Muscle fatigue during cross country sprint assessed by activation patterns and electromyographic signals time-frequency analysis - Zory, R.; Molinari, F.; Knaflitz, M.; Schena, F.; Rouard, A. (Scandinavian Journal of Medicine & Science in Sports, 2011)
The aims of this study were as follows: (i) analysis of activation patterns during the spurt of two heats of a cross country skiing sprint with the double poling technique and (ii) quantification of muscle fatigue of the investigated muscles. Eight elite skiers were tested and surface electromyographic signals (EMG) were recorded from seven muscles of the upper and lower limbs. For each subject and each muscle, the activation intervals were calculated for relying on a double-threshold statistical detector and the average rectified value was calculated on each activation interval. The detected activations were processed by a time-frequency algorithm in order to assess the progression of muscle fatigue. The EMG activation patterns and EMG amplitude highlighted no significant difference between the two spurts, despite a generally lower speed in the second spurt. The frequency analysis showed that upper body muscles are the first to be affected by fatigue and that clear signs of muscle fatigue appear right from the first spurt of the sprint simulation (i.e., biceps and triceps brachii) with a decrease in the instantaneous mean frequency. Biceps brachii activations and fatigue demonstrated the involvement of this muscle in propulsion.